Identifikasi Nilai Kosmologi Hindu Pada Bentuk Rumah Tradisional Bugis - Edy Semara Putra (Jurusan Dharma Acarya STAHN-TP Palangka Raya, 2022)
The Bugis traditional house as one of the results of high civilization culture is a product of the Bugis people's cosmological view of the philosophy of life in order to obtain harmony of life with nature. The belief system of the pre-Islamic Bugis people is considered to be related to Hinduism. This is illustrated in the belief in gods or gods, which are something that is considered an almighty, the creator of nature, determining the fate of man, fertilizing the land, and others. The relationship between the beliefs of the pre-Islamic Bugis people and Hinduism is traced from the identification of cosmological values in the architectural forms of traditional Bugis houses. This research uses qualitative descriptive method. Burke's theory of identification is used to trace the form, meaning and value of Hindu cosmology to the architectural form of traditional Bugis houses. The results showed that, the bugis traditional house has a structural form that is divided into three levels, namely: the top of the house (Rakkeang) has the meaning of the upper world (Botting Langi'); the body of the house (Alle Bola) has the meaning of middle-earth (Ale Kawa); and the bottom of the house has the meaning of the underworld (Uri Liyu). The identification of Hindu cosmology in the traditional Bugis house form shows a correlation between pre-Islamic Bugis beliefs and the concept of Hindu cosmology. This is shown from the concept of cosmology which divides the universe into three levels, namely: the upper world (the world of the gods), the middle world (the human world), and the underworld (the supernatural world). In addition, the concepts of constituents of the human body matter also have similarities, namely soil, water, fire, and air. The concept of cosmology is also a reference or basis for the Bugis community and Hindu society, especially Balinese, in building houses as a place to live.